The Urgency of Regulatory Reform in Order to Support Indonesia’s National Development - Wicipto Setiadi (University of Udayana, 2018)
Poor regulation quality contributes negatively to the regulation and law enforcement in the life of the state. The indicator of the poor quality of regulation includes, among others, the large number of regulations requested for judicial review and effectiveness of the implementation of regulations. There are several regulatory issues in Indonesia today, including the existence of multiple interpretations; potential conflict; overlap, principle mismatch, weak implementation effectiveness, not harmonious/out of sync; inconsistent; create unnecessary burdens, both on the target group and the affected groups. Base on these regulatory conditions, regulatory reform is very important and urgent. Given this very basic regulatory issue, it is necessary to make improvements in the regulatory field from upstream to downstream which leads to quality, orderly and simple regulations known as regulatory reform. The purpose of the study is to examine regulatory reform in order to support Indonesia's national development. research is done by doing literature research, or commonly known as the literature study. The Study shows that in order for a regulation to be good, it must fulfill several principles, namely: good norm, good process, and good drafting. Regulatory reform implementation is carried out through a) simplification of existing regulations; b) reconceptualization of the procedures for establishing regulations; c) institutional restructuring of regulation formation; and d) strengthening/empowering human resources with integrity. Good quality of democratic political dimension and progressive legal quality are needed to improve the quality of regulation